Israelite Festivals: From Cyclical Time Celebrations to Linear Time Commemorations - Farber, Zeʾev (Religions, 2019)
The Pentateuch and later Jewish tradition associates the key pilgrimage festivals with stories about Israel's past. Nevertheless, these festivals all began as agricultural or seasonal festivals. Using comparative evidence from the ancient Near East, and looking at the Covenant Collection, the earliest biblical law collection, through a redaction critical lens, we can uncover the early history of these festivals and even how they developed in stages. A similar process is evident with the Sabbath, which appears to have begun as a moon festival, as per certain biblical references and from comparative evidence, but which eventually developed into the seventh day of rest as part of the institution of the week, and then comes to be associated with the story of God resting after creation. These developments, from celebrating agricultural and lunar cycles to celebrating mnemohistorical events, can be seen as part of two parallel processes: the coalescing of Israelite cultural memory and the institution of the linear calendar as the dominant conception of time.